Harnessing the Power of Positive Reinforcement: A Creative Approach to Boosting Teacher Productivity - Irdiyansyah, Iyan; Partas, Yuyun Elizabeth; Jamani, Bildi Puji (JURNAL AL-TANZIM, 2024)
This study aims to improve teacher work productivity by strengthening school discipline and motivation. A quantitative approach was used in this study, along with correlation and survey methods. The study population was 195 teachers, and a sample of 131 teachers was randomly selected using the proportional random sampling method with standard and homogeneous data distribution. Data were collected through a questionnaire for validity and reliability through expert judgment and empirical tests. The findings of this study indicate that work discipline and teacher productivity have a positive and significant correlation (ry1) of 0.803, with a contribution (r²y1) of 64.5%. Work motivation and teacher productivity also have a positive and significant correlation (ry2) of 0.791, with a contribution (r²y2) of 62.5%. In addition, work discipline and work motivation have a positive and significant relationship (ry12) of 0.852, with a contribution (r²y12) of 72.5% to increasing teacher work productivity. The results of this study provide important implications for the development of managerial policies in schools, which should focus on improving teacher discipline and motivation to encourage work productivity. Schools need to design programs that strengthen both as key factors in improving the quality of education and student learning outcomes.